Effects of Copper nanoparticle supplementation on growth, intestinal morphology and antioxidant status in broilers exposed to cyclic cold stress - Abdullah, Saqib Saleem; Masood, Saima; Masood, Saima; Zaneb, Hafsa; Rabban, Imtiaz; Akba, Jamil; Hussain Kuthu, Zulfiqar (Emirates Journal of Food and Agriculture, 2022)
The purpose of this research was to determine the effects of copper nanoparticles (CuNP) supplementation on growth performance, intestinal morphology, intraepithelial lymphocytes (IELs), goblet cell (GC) count, stress hormones and oxidant/antioxidant balance of broilers exposed to cold stress. One day old broiler chickens (n=400) were allocated into five different groups and were raised under standard conditions until the 21st day. The five groups were designated as thermo-neutral (TN reared in 26°C), cold stress (CS raised under 13°C±2°C for 8 hours/day from d 22- d 35), CS5 (CS+ 5mg/kg diet CuNP), CS10 (CS+10mg/kg diet CuNP) and CS15 (CS+15mg/kg diet CuNP). On 35th day, 16 birds per group were selected randomly for blood collection and were then humanely sacrificed for tissue sample collection. CS group had a reduced (P<0.05) body weight (BW), villus surface area (VSA), villus height to crypt depth ratio (VH: CD) but had a higher (P<0.05) feed conversion ratio (FCR), goblet cell count, serum corticosterone and malondialdehyde (MDA) levels than the TN group. Inclusion of CuNP in diet linearly increased (P<0.05) BW, VH, VW, CD, VSA and GC count in jejunum and ileum. Conversely, MDA and corticosterone hormone levels and FCR, decreased linearly (P<0.05) with CuNP supplementation. In conclusion, during cold stress conditions, CuNP is a valuable feed additive in broilers with positive effects on growth performance and intestinal morphology